A JUSTIFIED GRAPH ANALYSIS OF PRAYER SPACE IN FLOODED HOMES - Zakiah Hidayati (Journal of Islamic Architecture, 2023)
Indonesia's risks of natural disasters force its people to live and adapt. It happens in Samarinda's urban settlements, which flood annually. Indonesia, a religious country, applied religion to most aspects of life. The religious element is persistent even in homes being inundated by floods. Devout Muslims consistently perform the five daily Shalah and sometimes Sunnah prayers in flooded conditions. This paper analyzed the spatial configuration of the Muslim prayer space in the flooded residence from different phases. The study method was based on Justified Graph analysis, and the sample was a stilt house in some periods. The research locus was in the most settlement area covering frequent floods. This research found that Integration and Mean Depth were the critical factors in prayer spaces in flooded homes due to the connection with other spaces, visual control, and interaction. Muslim home renovations should have a prayer space with high Integration value and low Mean Depth. High Integration connects the prayer space to numerous rooms, making controlling and interacting with others during a flood easier. Low Mean Depth allows easy access to the prayer space from the main entrance. A prayer space will ensure the house has a safe area during a flood.